Photoinduced Electron Transfer in a Zinc Phthalocyanine–Fullerene Conjugate Connected by a Long Flexible Spacer - Lederer, Marcus; Ince, Mine; Victoria Martinez-Diaz, M.; Torres, Tomas; Guldi, Dirk Michael (ChemPlusChem, 2016)
A hexadodecyl-substituted zinc phthalocyanine covalently linked through a flexible spacer to a fullerene—ZnPc−C60—has been investigated regarding electron transfer from the photoexcited, electron-donating ZnPc to the electron-accepting C60. While ground-state interactions between electron donor and acceptor within ZnPc−C60 could not be detected via steady-state absorption spectroscopy, clear proof for excited-state interactions came from steady-state fluorescence spectroscopy. To this end, the fluorescence in ZnPc−C60 is strongly quenched with quantum yields in THF as low as 0.05. Insight into excited-state electron-transfer deactivation within ZnPc−C60 came from time-resolved femtosecond transient absorption spectroscopy. For example, upon exclusive excitation of the phthalocyanine within the ZnPc−C60 conjugate, a set of transients evolve featuring, on the one hand, the signature of the one-electron oxidized ZnPc radical cation and, on the other hand, of the one-electron reduced C60 radical anion. The analysis of the corresponding dynamics in chlorobenzene resulted in lifetimes for charge-separation and charge-recombination of 7.4 ps and 2.2 ns, respectively.
CRIS-Team Scopus Importer:2023-03-07
Keywords: fullerenes; liquid crystals; photoinduced charge transfer; phthalocyanines